Pengaruh Perencanaan Anggaran, Biaya Standar, Pengendalian Biaya terhadap Efisiensi Operasional Perusahaan (Studi Kasus pada Perusahaan Food and Beverage di Indonesia) - Harahap, Salsabila Rahadatul Aisyi; Rafika, Mulya; Siregar, Muhammad Raja (SAFE-Network, 2025)
This study aims to analyze the effect of budget planning, standard costs, and cost control on the operational efficiency of food and beverage companies in Indonesia. This study uses a quantitative approach. The population of the study consists of all food and beverage companies listed on the Indonesia Stock Exchange. The sample obtained consisted of 10 companies engaged in the food and beverage sector, with a financial report period of five years, resulting in a total of 50 data points. The data used is secondary data obtained from financial reports listed on the Indonesia Stock Exchange. The data analysis technique in this study uses SPSS software to conduct classical assumption tests, multiple linear regression, and hypothesis tests. The results of the study indicate that, partially, the Budget Planning variable (X1) does not have a significant effect on Operational Efficiency with a significance value of 0.657 > 0.05. Meanwhile, the Standard Cost variable (X2) has a significant effect on Operational Efficiency with a significance value of 0.003 < 0.05, and the Cost Control variable (X3) also has a significant effect on Operational Efficiency with a significance value of 0.000 < 0.05. Simultaneously, Budget Planning, Standard Cost, and Cost Control have a significant effect on Operational Efficiency with a significance value of 0.000 < 0.05.